PERANAN KRITERIA OSEANOGRAFIS DALAM MERUMUSKAN SOLUSI DILEMA INTEGRASI KEBIJAKAN RUANG PESISIR DI WAHA RAYA - Asuhadi, Sunarwan; ., Hendrawanto; Deby, Rachmat; Wiyono, Edy (Jurnal Bahari Papadak, 2023)
Abstract - This study aims to encourage the use of oceanographic data as a basis for integrating spatial planning in coastal areas so that it becomes a fair synthesis for the RTRW, RZWP-3-K, and various other planning policies. The research data was obtained through literature study, both policy data, and oceanography. Data analysis was carried out descriptively by comparing the suitability of the spatial policy (RTRW Wakatobi Regency) with the condition of oceanographic factors in the Waha Raya coastal area. The results of the study show that oceanographic factors can be one of the criteria that determine the resolution of the Dilemma of the integration of coastal spatial planning policies, which so far tend to be ego-sectoral, including accommodating various space utilization needs, in the form of making technical design development in coastal areas. To minimize problems in spatial planning and management policies that have occurred so far, it is recommended that all spatial policies (RTRW, RZWP-3-K, RIPPDA, etc.) must be integrated, both administratively and functionally, especially coastal space as a slice area, one of which is by utilizing oceanographic data. Keywords : Oceanographic criteria, Dilemma of spatial policy integration, RTRW, RZWP-3-R